L’impossible guérison de Saül : Considérations sur le solo de harpe de l’oratorio Saul de Georg Friedrich Haendel et Charles Jennens (1739) - Pierre Degott (Etudes Epistémè)
The starting-point of this paper lies in the debate on the suitability of performing the harp solo given to the character of David in Handel’s Saul (1739). Rejected by certain editors, the passage is supposed to represent the healing of Saul by David and should as such be regarded as a significant piece in the economy of the work. First examined in the light of the aesthetic contexts of the oratorio, the piece is also studied from an historical and political perspective. Ruth Smith has thus shown how the Saul/David succession in the Bible could be seen as an allegorical representation of the Hanoverian succession. Without going so far as to adhere to the theories of the Lebanese historian Kamal Salibi, according to whom the Saul/David relationship was of a homosexual nature, one may wonder to what extent the intimacy of the healing act could actually be shown and performed within the usual codes of suitability and decency. In this respect Barrie Kosky’s recent staging of Handel’s work allows us to enrich and enlarge our perspective.